A reasonably large review of operationalization in child maltreatment research: Assessment approaches and sources of information in youth samples. (January 2019) - Jackson, Yo; McGuire, Austen; Tunno, Angela M.; Makanui, P. Kalani
Abstract: Child maltreatment research varies considerably in how maltreatment is measured. Although researchers have advocated for improvements in maltreatment assessment, a first step is a clear understanding of the status on how the field operationalizes maltreatment. The current paper sought to achieve this goal through reviewing research on child maltreatment over a recent 10-year span to identify trends in maltreatment assessment and operationalization. Information on maltreatment measurement was extracted from 338 articles across three major journals devoted to publishing research on child maltreatment. Among the various definitional dimensions of maltreatment, type was the most common way maltreatment was operationalized, followed by severity, frequency, and chronicity, a stable trend across the 10-year span of review. The results indicated that the majority of studies measured maltreatment as consisting of multiple types, although some studies focused on one type of maltreatment as the indicator of child maltreatment. Further, the most common assessment method was the administration of a questionnaire or the combination of two questionnaires with the second most common being summaries from case file review. Recommendations for future research are discussed.